2016
DOI: 10.5586/asbp.3503
|View full text |Cite
|
Sign up to set email alerts
|

Methyl jasmonate-induced accumulation of metabolites and transcriptional responses involved in triterpene biosynthesis in Siraitia grosvenorii fruit at different growing stages

Abstract: The cucurbitane-type triterpenoid glycosides, mogrosides, are the main active components of Siraitia grosvenorii fruit. Squalene and cucurbitadienol are among the intermediates of the biosynthetic pathway for the formation of cucurbitanetype triterpenoid backbones of mogrosides. It is recognized that the exogenous application of methyl jasmonate (MeJA) increases the accumulation of secondary metabolites in various plant species. Here, the effect of MeJA (50, 200, and 500 μM) on the accumulation of squalene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
(60 reference statements)
1
4
0
Order By: Relevance
“…Further analysis revealed that Cu in the soil was significantly correlated with the ginsenosides content and the activity of CYP450 in ginseng of different plant ages, suggesting that Cu has a positive effect on ginseng growth [ 10 ]. These results were consistent with the important role of copper in CYP450, which could activate the CYP450 enzyme [ 37 , 38 ]. Moreover, a linear relationship suggested that heavy metal content in soil could predict ginsenosides, Cu and As content in ginseng.…”
Section: Discussionsupporting
confidence: 87%
“…Further analysis revealed that Cu in the soil was significantly correlated with the ginsenosides content and the activity of CYP450 in ginseng of different plant ages, suggesting that Cu has a positive effect on ginseng growth [ 10 ]. These results were consistent with the important role of copper in CYP450, which could activate the CYP450 enzyme [ 37 , 38 ]. Moreover, a linear relationship suggested that heavy metal content in soil could predict ginsenosides, Cu and As content in ginseng.…”
Section: Discussionsupporting
confidence: 87%
“…It has been found that exogenous plant hormone, like methyl jasmonate, abscisic acid, and salicylic acid, could affect the accumulation of secondary metabolites in Salvia miltiorrhiza [30], Glycyrrhiza uralensis root [31], and Uncaria tomentosa [32]. Exogenous plant hormone applied in the S. grosvenorii might be an appropriate approach for good production, and Zhang et al demonstrated that methyl jasmonate applied in different development stages of S. grosvenorii fruit significantly promotes the accumulation of squalene, cucurbitadienol, and mogrosides IIE [33].…”
Section: Discussionmentioning
confidence: 99%
“…Three intermediates (squalene, cucurbitadienol, and cycloartenol) were measured. The fruit samples for GC-MS analysis were prepared and the basic operational conditions were as described previously [13,33]. Helium gas was used as the carrier gas, and the carrier flow rate was 1.5 mL min −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the gene annotation of the transcriptome, 104 unigenes were identified and their responses to MeJA induction were investigated involved in the biosynthesis of indole, terpenoid and phenylpropanoid [ 30 ]. The results showed that transcriptional levels of SgHMGR , SgSQS , SgCS and SgCYP450 were up-regulated and their responses in the presence of MeJA were related to the concentration and timing of MeJA treatment in Siraitia grosvenorii [ 31 ]. MeJA-regulated rubber biosynthesis, based on a differential expression analysis, showed that the expression of HMGCR , FPPS , IDI , GGPPS , REF/SRPP and transcription factors (bHLH, MYB, AP2/EREBP and WRKY) increased with MeJA treatment in TKS [ 32 ].…”
Section: Introductionmentioning
confidence: 99%